Perancangan Sistem Informasi Akademik Pada SMA Muhammadiyah 25 Berbasis Web - Falda Khoulika; Kussigit Santosa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Muhammadiyah 25 Pamulang High School is a school with national standards with hundreds of students. The large number of students at SMA Muhammadiyah 25 Pamulang certainly makes it difficult for the school officer to collect academic data for reporting purposes to the student parents.Web-Based Academic Information System for SMA Muhammadiyah 25 Pamulang is an information system that provides academic data for SMA Muhammadiyah 25 Pamulang students. The making of this information system is done by collecting data, analyzing, designing, implementing, testing the information system, and the object of research in this case is SMA Muhammadiyah 25 Pamulang. This information system is made using the PHP programming language and the Laravel framework. The Results of this final project is the Academic Information System of SMA Muhammadiyah 25 Pamulang that can be used to facilitate school employees in processing student data and as a medium of information for parents of students regarding the academics of their sons and daughters.